PENGARUH TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rachman, Muhammad Zauqi (Directorate of Academic Research and Community Services, 2020)
This research aims to get the empirical evidence about the factors which will affect earnings management in manufacturing companies that listed in Indonesia Stock Exchange. These factors are audit committee financial expertise, institutional ownership, board size, ownership concentration, foreign directors, and board activity. Discretionary accrual is used as the proxy of earnings management. 101 manufacturing companies which listed in Indonesia Stock Exchange during period year 2014 to year 2016, was used as sample using purposive sampling method. This research uses multiple regression as a method of data analysis. The result shows that audit committee financial expertise, institusional ownership, board size, ownership concentration and foreign directors have no effect to earnings management, while board activity affects earnings management.